Eff ect of gamma rays on germination, morphological and yield characters of bhendi (Abelmoschus esculentus [L.] Moench) - P. Pavadai, R. Elangovan, (Horticultural Biotechnology Research, 2015)
Bhendi (Abelmoschus esculentus [L.] Moench) is the most common vegetable crop of the world. The genusÂ Abelmoschus belongs to family Malvaceae is represented by 12 species. This investigation was carried out toÂ the study of different doses of gamma irradiation on bhendi seeds of varieties arka anamika. Gamma irradiationÂ treatment at 10, 20, 30, 40, 50, and 60 KR levels. The main objective of the present study is to determine theÂ effect gamma irradiation on different morpho-agronomic characteristics. Agronomic traits were analyzed suchÂ as days of first flower, height of plants, number of fruits per plant, fruit length, seed yield per plant, fresh weightÂ per plant, dry weight per plant, 100 seed weight. The seed pre-soaked in distilled water for 6 h before the sownÂ in the field. The results showed that the positive shift with respect to all parameters. High doses of gamma irradiation (40 and 50 KR) observed in moderate to high values.